2019
DOI: 10.1002/jrs.5738
|View full text |Cite
|
Sign up to set email alerts
|

In situ conversion monitoring of styrene emulsion polymerization by deconvolution of a single reference band near 1,000 cm−1

Abstract: Styrene emulsion polymerization was performed in batch reactor using Raman spectroscopy for in situ monitoring of styrene conversion. The variation of the band of trigonal aromatic ring breathing at 1,000 cm−1 was analyzed in detail as a function of monomer conversion (wavenumber, integrated intensity, and half‐width at half‐maximum). The observed variation was described both qualitatively and quantitatively by a model assuming that the overall signal resulted from the addition of two close and distinct Gaussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Cui et al [ 189 ] described a real‐time Raman analysis of cleaning solution and applied it to the determination of residues in a cleaning mixture. Dropsit et al [ 190 ] demonstrated in situ conversion monitoring of styrene emulsion polymerization by deconvolution of a single reference band near 1000 cm −1 . They showed experimentally that information about monomer to polymer conversion could be obtained by applying linear modeling of the mixture to a single band of the Raman spectrum, which provided an alternative method of using a ratio of integrated intensities.…”
Section: Raman Techniques and Methodsmentioning
confidence: 99%
“…Cui et al [ 189 ] described a real‐time Raman analysis of cleaning solution and applied it to the determination of residues in a cleaning mixture. Dropsit et al [ 190 ] demonstrated in situ conversion monitoring of styrene emulsion polymerization by deconvolution of a single reference band near 1000 cm −1 . They showed experimentally that information about monomer to polymer conversion could be obtained by applying linear modeling of the mixture to a single band of the Raman spectrum, which provided an alternative method of using a ratio of integrated intensities.…”
Section: Raman Techniques and Methodsmentioning
confidence: 99%
“…In-line measurements via Raman spectroscopy are nondestructive, need no preparation, and are only slightly affected by scattering of water below a Raman shift of 2750 cm –1 . Thus, Raman spectroscopy represents an established process analytical technology (PAT) tool for various applications in polymerization, most prominently in emulsion polymerization and precipitation polymerization. , …”
Section: Introductionmentioning
confidence: 99%
“…In [9], the polymerization of styrene using bulk, emulsion and mini-emulsion polymerization is followed using Raman spectroscopy by computing the ratio between the area of the Raman peaks of the C=C double bond band and the aromatic band. Dropsit and coworkers [10] monitor the conversion of a styrene emulsion polymerization by analyzing the aromatic ring breathing at 1000 cm -1 as the contribution of styrene monomer and styrene polymer. These works use either peak integration methods, i.e., analyzing single peaks or PLS regression.…”
Section: Introductionmentioning
confidence: 99%